(untitled) (Numerus academy review, 2026)
The crime of violence against women has occupied Algerian society as a result of its violation of the most fundamental rights that women enjoy, which is their right to physical integrity, and their gravity is embodied in the attack on the weakest element in society, which is women, which leads to severe damages, whether at the private level of the woman and her family, or at the general level through The breach of security and general stability of society. The crime of violence against women is old in its roots, however, with the repetition of this phenomenon, it has become a phenomenon that affects all societies of the world, and given the spread of this phenomenon, the Algerian legislator has criminalized it and imposed a series of sanctions on it in the new amendment No. 15/19. Especially since the latter - the crime of marital violence against women - has become one of the forms of family violence, a social and human phenomenon known throughout history, and given the growing phenomenon, international and national legislation has to face it in all its forms, whether it is physical, psychological, economic or sexual violence The reality of the husband against the wife. And he has the problem posed in this case: Are the crimes brought by the Algerian legislator sufficient to deter crimes against women by the husband and how effective are they? . We will try to answer this problem through this study by adopting the following division: The first axis: protecting the wife from the physical and economic violence of the husband. The second axis: protecting the wife from the husband’s psychological and sexual violence.